2009
DOI: 10.1097/01.aoa.0000362102.64321.b9
|View full text |Cite
|
Sign up to set email alerts
|

Tocolytic Therapy: A Meta-analysis and Decision Analysis

Abstract: than weekly, dosing. A total of 1808 women at 80 centers in 20 countries who were between 25 and 32 weeks of gestation and had received an initial course of either betamethasone or dexamethasone because of a high risk for preterm delivery were randomized to receive subsequent courses of either betamethasone or placebo at 2-week intervals until delivery or 33 weeks of gestation. A variety of maternal and neonatal outcomes were evaluated.There were no significant beneficial effects of the multiple courses of ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
7

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(65 citation statements)
references
References 0 publications
0
58
0
7
Order By: Relevance
“…Indomethacin is well established as an effective tocolytic agent [1][2][3]. Indomethacin has a long track record in prevention of spontaneous preterm labor and more recently has been administered to prevent preterm labor during several types of midgestation fetal interventional procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Indomethacin is well established as an effective tocolytic agent [1][2][3]. Indomethacin has a long track record in prevention of spontaneous preterm labor and more recently has been administered to prevent preterm labor during several types of midgestation fetal interventional procedures.…”
Section: Discussionmentioning
confidence: 99%
“…The data on the use of magnesium sulfate as a tocolytic drug is controversial. Meta-analyses [11,12] showed that magnesium sulfate was an effective tocolytic in terms of prolonging the pregnancy by 48 hours compared to placebo (OR 2.46; 95 % CI: 1.58-4.94); however, this flies in the face of the results and statements of the 2014 Cochrane Review [15], which were generated using 37 studies with 3571 pregnant women. According to the Cochrane Review, magnesium sulfate was not more effective than placebo or even no therapy at prolonging pregnancy for more than 48 hours and does not reduce the rate of preterm births.…”
Section: Drugsmentioning
confidence: 99%
“…70 Nifedipine and other calcium channel blockers have been shown to have favorable efficacy and safety profiles for the acute treatment of preterm labor. 71 Nifedipine undergoes metabolism by CYP3A enzymes in the liver and gastrointestinal tract. Nifedipine clearance is increased in pregnancy, due to increased CYP3A.…”
Section: Systems Pharmacology Studies May Provide Insight Intomentioning
confidence: 99%
“…Prostaglandin inhibitors, such as indomethacin, are also effective for the acute treatment of preterm labor. 71 Indomethacin is primarily metabolized by the CYP2C9 enzyme. The CYP2C9*2 and *3 poor metabolizer haplotypes may lead to decreased indomethacin clearance in 10-20% of white patients and up to 6% of black patients.…”
Section: Systems Pharmacology Studies May Provide Insight Intomentioning
confidence: 99%